Analytical Solution for the Cost Optimal Electric Energy Storage Size Based on the Effective Energy Shift (EfES) Algorithm - Fellerer, Jonathan; German, Reinhard (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2024)
The importance of Electric Energy Storage (EES) for the transformation to an energy grid with a large share of Renewable Energy Source (RES) has been studied and shown for many decades. While larger storage systems might provide more energetic benefits for the overall grid, they also require higher investment and capital costs. Hence the question of the cost-optimal size of EES and RES is commonly stated in public debates and the related literature. This minimization problem is mainly solved by combining simulation and optimization methods. Even though this enables the analysis of highly complex scenarios, the configuration and computation time are high, and many of the found methods are not reproducible. Within our paper, we introduce an analytical solution for calculating the cost-optimal capacity of an EES that is derived from results computed by the Effective Energy Shift (EfES) algorithm.
CRIS-Team Scopus Importer:2024-11-15
Keywords: analytical solution; battery storage; dimensioning; electric energy storage; energy storage system; minimal costs; optimal capacity; renewable energy; sizing

Analytic Closed-Form Expressions for Energetic Measures as a Function of the Capacity of Electric Energy Storage - Effective Energy Shift Algorithm - Fellerer, Jonathan; Scharrer, Daniel; German, Reinhard (Social Science Research Network, 2024)
The Renewable Energy Sources wind and solar are key drivers for the transition to a greenhouse gas neutral economy.However, they pose the inherent problem of high fluctuation in their availability, thereby affecting the consistency of energy generation.Electric Energy Storage systems are a key technology for solving many of the emerging challenges.As these entail their own investment costs, the added benefit of these systems has to be calculated.Typical energetic measures are self-sufficiency, self-consumption and the loss-of-load probability.The considered energy system possesses some form of renewable energy generation, an intrinsic energy demand and a potential Electric Energy Storage.This paper presents an algorithm that uses time series for the demand and renewable generation to construct an analytic solution and closed-form expression and its parameters for the named energetic measures as a function of the usable capacity of the Electric Energy Storage.To be able to compute those functions, new system properties, called "effectiveness" and "gain", are introduced, derived and suggested as new, more general key performance indicators.Power limits, charging and discharging efficiencies, and efficiencies for the direct use of generation by the system can be considered.Since no simulation or optimization is required to perform the analysis, it is computationally efficient and easy to set up with a relatively small amount of input data
Keywords: analytic closed-form expression; electric energy storage; renewable energy; self-sufficiency; self-consumption; effectiveness

Integration of Fault Tree Analysis into Model-Based Product Line Engineering in Railway Vehicles - Dibaei Asl, Mahdi; Fellerer, Jonathan; Arestova, Anna; Hielscher, Kai-Steffen; German, Reinhard (2024 the 8th International Conference on System Reliability and Safety (ICSRS), 2025)
Reliability analysis based on fault trees is one of the important methods for determining the cause of system failure by beginning from the top event and proceeding to the basic events, however, it is usually overlooked in the first stages of designing complex systems. The main reason is the requirement for in-depth knowledge about the characteristics and behavior of the system. This study provides a solution for reliability analysis by generating fault trees based on Model-Based System Engineering (MBSE) and Product Line Engineering (PLE). System Modelling Language (SysML) diagrams are leveraged to detect and model failure points of the system and to map them into fault trees. Moreover, to develop the proposed solution for product families and detect variability-related failure points from PLE, we use pure::variants diagrams to develop fault trees. To investigate the validity of the proposed approach, as a case study, we present the process of fault tree generation from SysML and pure::variants diagrams in railway vehicles. Finally, a number of important challenges and limitations are explained briefly.<br
Keywords: Reliability analysis; Fault tree analysis; Model-based system engineering; Product line engineering

Wasserstoff in der Metropolregion Nürnberg – Analyse der Kompetenzen, Chancen und Herausforderungen - Pircher, Thomas; Bazan, Peter; Elhaus, Nora; Fellerer, Jonathan; German, Reinhard; Karl, Jürgen; Kolb, Sebastian; Kunz, Thomas; Opferkuch, Frank; Pilz-Lansley, Alexander; Reichenwallner, Simon; Ronge, Karlheinz; et al. (2023)
The study shows that the metropolitan region has economic potential in the product-related value chain. Depending on the scenario, this market sector can become a decisive factor and will create jobs in several fields in the European Metropolitan Region Nuremberg (EMN). However, the simulations show that the generation potential from energy surpluses is not sufficient for significant export. However, the own production of hydrogen in the metropolitan region could cover the own demand, mainly heavy duty vehicles and process heat, and thus could also be an incentive for the own infrastructure development. However, the simulation clearly shows that a pushed expansion of renewable energies is indispensable and that the storage capacities and concepts planned so far will not be sufficient to buffer the surplus energy peaks and make them available. There is a need for research and action here, both specifically for the EMN and for other regions. From our point of view, it will be crucial for the EMN that the existing industry in the EMN acquires the competences to develop and produce components, partial and complete systems for hydrogen technology. For this purpose, it is important to provide easy access to this knowledge in the form of a central knowledge center and to ensure close networking of the various players in the product-related value chai
Keywords: hydrogen; european metropolitan area; mobility; sector coupling